Attribute grammar applied to human activities recognition in intelligent environments - Freitas, Leandro O. (2020)
© Springer Nature Switzerland AG 2020. Researches about context awareness have been growing in the past decades. The development of services that considers the context of users are getting popular and are gaining more functionalities, making them smarter. One of the most common features is the monitoring of activities through a diversity of sensors. Yet, this is still superficial monitoring where the devices lack information sharing. Intelligent environments aim the exchanging of information with the purpose of creating models that represent real-world situations. This paper describes the use of an attribute grammar in order to create a formal specification of situations in such domains. The problem of representation of human activities is tackled through a case study to demonstrate how attribute grammar can help the improvement of this process.